Answer:
<em>( 4, 11 ) , ( - 4, 27 ) </em>
Step-by-step explanation:
f(x) = x² - 2x + 3
f(x) = - 2x + 19
x² - 2x + 3 = - 2x + 19
x² - 16 = 0
( x + 4 )( x - 4 ) = 0
= - 4
= 4
f(x) =
= - 2( - 4 ) + 19 = 27
= 27
f(x) =
= - 2( 4 ) + 19 = 11
= 11
<em>( 4, 11 ) , ( - 4, 27 )</em>
You need to substitute the x and y values into the original and subtract 15 from each side to get b. You should get a b value of -20
Answer:
Arithmetic
Step-by-step explanation:
Arithmetic is additive and geometric is multiplicative, and the numbers aren''t multiplying, they're adding.
We have two points so we can find the gradient using y1-y2/x1-x2
gradient = 21-27/2-8
= 1
we know the form for any linear equation is y = mx + c
we have m and a point so we can substitute in point (2,21) to find c
21 = 1 x 2 + c
c = 19
therefore, the equation is y = x + 19